International Customary Law in the Jurisprudence of the ICTY and the ICTR - Konderla, Joanna (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The object of this article is to describe how two ad hoc international criminal tribunals dealt with the issue of following and explaining norms of customary international law. In order to do that the representative decisions and judgments of international criminal courts are citied and examined. The first part is a description of the sources of law for criminal tribunals, with emphasis on the international custom. The second consists of the analysis of the international criminal courts’ approach to the two-element theory of customary international law. It is followed with an enquiry into the content of customary international law: concerning both jurisdiction and substance of customary international law.
Keywords: International Customary Law; ICTR; ICTY; jurisprudence